Answer:
d. x=4
Explanation:
So we have the following equation:
![log_((3x-7))25=2](https://img.qammunity.org/2023/formulas/mathematics/high-school/w09ab67ttji2q0o9ul6iqu0v45uv3pc3iy.png)
Now to understand how we can rewrite this equation, let's go over the definition of a log:
![log_ba=x\implies b^x=a](https://img.qammunity.org/2023/formulas/mathematics/college/p4ze3zjh6mcpnzgu98i9hwsirbdn9e1v0u.png)
So this value of "log base b of a" Is equal to the value that I have to raise the base b to, to get the result a
So when I have the equation:
![log_((3x-7))25=2](https://img.qammunity.org/2023/formulas/mathematics/high-school/w09ab67ttji2q0o9ul6iqu0v45uv3pc3iy.png)
This is essentially saying, I have to raise (3x-7) the base, to the power of 2, to get the result of 25
So let's rewrite it using the definition of a log
![(3x-7)^2=25](https://img.qammunity.org/2023/formulas/mathematics/high-school/7shocao3n2l254a6f4fva24x7iwpkvkz9n.png)
Take the square root of both sides
![3x-7=5](https://img.qammunity.org/2023/formulas/mathematics/college/k9mvn0yl1hokydhey106fae000piygxmm1.png)
add 7 to both sides
![3x=7+5](https://img.qammunity.org/2023/formulas/mathematics/high-school/1upajvp98tr8zu4ch9m5u3p13e1c2njo7d.png)
Now divide both sides by 3
![x=(7\pm5)/(3)](https://img.qammunity.org/2023/formulas/mathematics/high-school/5uj34gncrbpo80qub1i7zgzw4f3qrj8pjs.png)
Simplifying:
![x=4](https://img.qammunity.org/2023/formulas/mathematics/college/clnezaiwnjqx862gnqh94au9b279p8untt.png)